Analisis Pengaruh Gaya Kepemimpinan Konsultatif dan Beban Tugas terhadap Tingkat Komitmen Karyawan di PT. Bank BCA KCP Bali - Susilo, Edi; Sulistyawati, Upik Sri (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
This research aims to investigate the influence of consultative leadership style and task demands on employee organizational commitment at PT. Bank BCA KCP Bali, as well as to measure the extent to which leadership and task demands influence the organizational commitment of employees at PT. Bank BCA KCP Bali. This research was carried out at PT. Bank BCA KCP Bali with a research object population involving all employees. The number of respondents involved was 53 people. The results of the F-test (simultaneous) show that all the variables studied have a significant influence on increasing the commitment of PT employees. Bank BCA KCP Bali, with an F-calculated value that exceeds the F-table value at a significance level of □= 5%. Partially, the t-test results show that the most significant variable influences the commitment of PT employees. Bank BCA KCP Bali is a task demands variable, with a t-count value that is greater than the consultative leadership variable which has a smaller t-count value.